ประสบการณ์การดูแลตนเองของหญิงไทยมุสลิมที่ถือศีลอดระหว่างตั้งครรภ์ - มาลี แซ่อุน (จุฬาลงกรณ์มหาวิทยาลัย, 2005)
The purpose of this study was to explore self-care experiences in Thai-Muslim women practicing Ramadam fasting during pregnancy. A qualitative research methodolgy guided by Husserl Phenomenology was applied in this study. Participants were 16 Thai-Muslim pregnant woman, who practiced Ramadan fasting during October and November 2004 and received antenatal care in Yala hospital. Data were collected by in-depth interview. The interviews were tape recorded and transcribed verbatim. The content analysis method was applied for data analysis. Findings revealed that self-care experiences in Thai-Muslim women practicing Ramadan fasting during pregnancy consisted of 3 themes, including 1) the meaning and the important of Ramadan fasting comprised Fasting is obligatory, Fasting is precious and blessing, Fasting is practice to strengthen one{7f2019}s body and mind, and Fasting has spiritual benefits, 2) four categories of self-care practice during Ramadan fasting which were care of nutrition, work and daily activity, rest, and care of mind. The emphasis was placed on nutrition practices, and 3) two stages of adaptation to fasting were stage of initiation (1-3 days) and stage of practice (after 3 days). The major adaptation was to rest as much as possible, however, the discontinues of fasting was decided if anything went wrong. This study provided better understanding about the Ramadan fasting experience in Thai-Muslim during pregnancy. Finding can be used for developing holistic nursing interventions that can effectively meet the need of Thai-Muslim women practicing Ramadan fasting during pregnant.